Analysis and design method of a combined radial–axial magnetic bearing based on asymmetric factor. Issue 5 (19th March 2019) - Ren, Xiaojun; Sun, Jinji; Peng, Cong; Qiao, Hong
Abstract : Combined radial–axial magnetic bearings (MBs) use a common bias magnetic circuit to provide radial and axial bias magnetic flux. Different from separate MBs, there is a constraint relation between the radial and axial bias flux. Meanwhile, there is also a constraint relationship between the radial and axial maximum bearing capacity. Therefore, the design method for separated MB is not suitable for a combined radial‐axial MB (CRAMB). In this study, a design method of the CRAMB based on an asymmetric factor was proposed. The definition of the asymmetric factor was proposed. In order to avoid the radial and axial magnetic flux into the weak magnetic field and saturation region, the optimum range of the asymmetric factor is analysed. The influence of the asymmetry factor on stiffness is analysed; the prototype designed by this method can run stably. The validity and accuracy of the design method are verified by experimental results.